Pendampingan Prosedur Keselamatan Kerja pada UMKM Produksi Furniture CV Rumah Menyala di Kabupaten Batang - Hermawan, Agung; Maulana, Jaya; Irawan, Teguh; Maula, Muhammad Fatih Izzul (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The furniture industry is a strategic commodity supporting national foreign exchange. Indonesia has great potential in developing this industry, supported by the availability of raw materials such as wood, rattan, and bamboo and an abundant workforce. However, workplaces in this sector, both formal and informal, have various potential hazards that can affect the health and safety of workers. This research aims to provide stimulus in the form of Personal Protective Equipment (PPE) and work safety signs to CV Rumah Menyala furniture MSMEs in Tegalsari Village, Kandeman, Batang, to improve worker safety and health. This activity includes the formation of an Occupational Safety and Health Advisory Committee (P2K3), education regarding hazard and risk mapping, and preparing work safety SOP documents. The activity results show increased worker awareness regarding the importance of using PPE and managing work safety. However, ongoing efforts are still needed to implement work safety SOPs with discipline. In this way, it is hoped that the risk of occupational diseases and work accidents can be minimized to increase worker productivity